Arachnoid Cysts of the Internal Auditory Canal: Multiplanar Magnetic Resonance Imaging With Audio‐Vestibular Correlates. (21st June 2021) - Di Stadio, Arianna; Dipietro, Laura; Messineo, Daniela; Ralli, Massimo; Ricci, Giampietro; Greco, Antonio; Brenner, Michael J.
Abstract : Objectives/Hypothesis: To investigate prevalence, radiological characteristics, and functional correlates of arachnoid cysts (AC) of the internal auditory canal (IAC) region, including associations of nerve compression with auditory/vestibular symptoms and asymmetrical audiogram or vestibular testing. Study Design: Retrospective study. Methods: T2‐weighted magnetic resonance imaging (MRI) studies of IACs were retrospectively analyzed from 1247 patients with asymmetric auditory or vestibular symptoms. Patients with radiological findings of AC of the IAC were identified. Multiplanar analysis was used to analyze cyst position in the IAC and assess nerve displacement or compression. Size, position, and presence of nerve compression were correlated with symptoms. Results: Twenty‐four patients had a cyst in the middle or fundus in the IAC. Diameter ( P  = .04) and position ( P  = .002) of AC were associated with symptoms. Sagittal analyses identified displacement versus compression ( P  = .003) more reliably than axial imaging. Symptom laterality was associated with the site of radiological abnormality. Vestibular nerve compression was associated with vertigo ( P  = .0001), and cochlear nerve compression was associated with auditory symptoms ( P  < .0001). Conclusions: In a retrospective series of patients undergoing MRI of IACs for asymmetric auditory or vestibular impairment, clinical symptom profile correlated with blinded assessment of IAC lesions. Level of Evidence: 4 Laryngoscope, 131:2323–2331, 2021